Toward Stable Superbenzoquinone Diradicaloids - Li, Guangwu; Phan, Hoa; Herng, Tun Seng; Gopalakrishna, Tullimilli Y.; Liu, Chunchen; Zeng, Wangdong; Ding, Jun; Wu, Jishan (Angewandte Chemie International Edition, 2017)
Superbenzoquinone (SBQ) is a quinone derived from a classic polycyclic aromatic hydrocarbon (PAH), hexa‐peri‐hexabenzocoronene (so‐called “superbenzene”), and is a challenging synthetic target. Herein we report the successful synthesis and characterization of its derivatives. We reveal that the high reactivity of SBQ is due to its intrinsic open‐shell diradical character. Thus, two kinetically blocked SBQs, SBQ‐Me and SBQ‐Ph, were prepared by different synthetic strategies. 4‐tert‐Butylphenyl‐substituted SBQ‐Ph demonstrated good stability and could be isolated in crystalline form. Both compounds have an open‐shell singlet ground state and show thermally populated paramagnetic activity. Our studies provide effective strategies toward stable quinone‐based diradicaloids. As captivating as a butterfly: Different strategies toward stable superbenzoquinone (SBQ) derivatives were explored, and stable 4‐tert‐phenyl‐substituted SBQ‐Ph was obtained by appropriate kinetic blocking. SBQ‐Ph (see structure) has an open‐shell singlet ground state with moderate diradical character and adopts a butterfly‐like geometry in the single crystal.